2020 IEEE International Symposium on Information Theory (ISIT) 2020
DOI: 10.1109/isit44484.2020.9174355
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Privacy-Signaling Games and Payoff Dominant Equilibria

Abstract: We consider a privacy-signaling game problem in which a transmitter with privacy concerns and a receiver, which does not pay attention to these privacy concerns, communicate. In this communication scenario, the transmitter observes a pair of correlated random variables which are modeled as jointly Gaussian. The transmitter constructs its message based on these random variables with the aim to hide one of them and convey the other one. In contrast, the objective of the receiver is to accurately estimate both of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…For discrete RVs they provide a numerical algorithm to find an equilibrium whereas for Gaussian RVs, a bound on the estimation error is provided and affine policies are shown to achieve this bound. In [9], a privacy-signaling game problem for the setup in Fig. 1 is considered in which a transmitter with privacy concerns observes a pair of correlated random vectors which are modeled as jointly Gaussian.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…For discrete RVs they provide a numerical algorithm to find an equilibrium whereas for Gaussian RVs, a bound on the estimation error is provided and affine policies are shown to achieve this bound. In [9], a privacy-signaling game problem for the setup in Fig. 1 is considered in which a transmitter with privacy concerns observes a pair of correlated random vectors which are modeled as jointly Gaussian.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Remark 3.2: (Connection to similar work) In [9], a similar setup is considered in which the random sources are jointly Gaussian, and the squared error is utilized as privacy and information exchange metric. Similar to our result, it is shown that Stackelberg and payoff dominant Nash equilibria coincide.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations